2021
DOI: 10.1021/acs.jpcc.0c05478
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure and Transport Properties of Single-Molecule Junctions with Different Sizes of π-Conjugated System

Abstract: We investigated the electronic structure and charge transport properties of single-molecule junctions of a series of acene-type molecules (i.e., pyrazine, quinoxaline, and phenazine) with different sizes of the π-conjugated system using a scanning tunneling microscopy-based break junction method under ambient conditions. A combined statistical analysis of the electric conductance and current versus bias voltage (I–V) characteristics based on the resonant-level model revealed the size dependence of the electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…20 Yet few reports of pyrazine conductance are found in the literature and our own measurements show no discernible signal, as we show further below. 21,22 We reason that the absence of a reliable pyrazine conductance signature is due to the reordering of frontier MOs in pyz compared to benzene, as shown in Figure 1A, left column. The highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) of benzene consist of two degenerate MOs that all have π-character.…”
Section: Resultsmentioning
confidence: 99%
“…20 Yet few reports of pyrazine conductance are found in the literature and our own measurements show no discernible signal, as we show further below. 21,22 We reason that the absence of a reliable pyrazine conductance signature is due to the reordering of frontier MOs in pyz compared to benzene, as shown in Figure 1A, left column. The highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) of benzene consist of two degenerate MOs that all have π-character.…”
Section: Resultsmentioning
confidence: 99%
“…Triggered by sophisticated molecular design, understanding the underlying physics of materials at the molecular level, and realizing the rapid miniaturization trend in the semiconductor industry, single-molecule devices with outstanding transport properties have attracted a great deal of attention in recent years. [1][2][3][4][5][6][7][8][9] Obviously, the selection of single-molecule architectures between two electrodes is the basic prerequisite for constructing such devices with excellent performance. Due to their lower energies as well as unique structural and electronical properties, fullerene (C 60 ) is usually considered an ideal candidate for building the basic elements of such molecular-based devices.…”
Section: Introductionmentioning
confidence: 99%
“…35 Although when anchoring groups are involved, measurements have been limited to how an extension of the acenes along the long axis will affect the conductance perpendicular to the path of tunneling electrons as a function of acene length 36 where intermolecular effects and junction geometries play important roles. Another related example by Fujii 37 showed that the conductance of heteroatom acenes (pyrazine, quinoxaline, and phenazine) are not only size dependent but also molecular 38,39 propose a magic ratio rule (MRR) showcasing that the connectivity-driven conductance ratio of graphene-like aromatic molecules is simply the square of the ratio of two "magic integers" whose values depend only on the connectivities to the electrodes. Density functional theory (DFT) calculations results by Palma 41 demonstrate that acene derivatives have near length-independent conductance and the anchoring configuration (steric effect) could dominate the conductance behavior.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Although when anchoring groups are involved, measurements have been limited to how an extension of the acenes along the long axis will affect the conductance perpendicular to the path of tunneling electrons as a function of acene length where intermolecular effects and junction geometries play important roles. Another related example by Fujii showed that the conductance of heteroatom acenes (pyrazine, quinoxaline, and phenazine) are not only size dependent but also molecular orientation sensitive in the Au–molecule–Au junctions. Still, studies on the regio-effects on the single molecule conductance of PAHs anchored between electrodes are limited to a few examples. Lambert et al , propose a magic ratio rule (MRR) showcasing that the connectivity-driven conductance ratio of graphene-like aromatic molecules is simply the square of the ratio of two “magic integers” whose values depend only on the connectivities to the electrodes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation